The Effectiveness of Project-based Multi-representation Discourse on Junior High School Students’ Science Process Skills - Safitri, Mutiara; Susongko, Purwo; Hayati, Muriani Nur (Unnes Science Education Journal, 2020)
The purpose of this study was to determine the effectiveness of the implementation of Project-based Multi-Representation Discourse model in improving students’ science process skills. The method used was the quasi-experiment with pretest-posttest control group research design. The population in this study was VII graders of SMP N 17 Tegal. The sample was selected using the cluster random sampling techniques. The data were taken through tests, questionnaires, and documentation. The results showed that the students learning using the Project-based Multi-Representation Discourselearning model had an average N-gain percentage of 72.27%. The percentage score was higher than the students studying using the Multi-Representation Discourse (MRD) learning model which had an average N-gain percentage of 42.50%. The results of the data analysis showed that the Project-based Multi-Representation Discourselearning model is effective enough to be applied and has an effect on improving science process skills.